Textile tectonics - Spuybroek, Lars, ....-; Georgia Institute of Technology. College of Architecture (Rotterdam : NAi Publishers, 2011)
Textile tectonics" reveals how natural, ornamental and folkloristic patterns - from the veins of leaves to Gothic rose windows, from foam formations to traditional styles of hair braiding and from Celtic knotwork to knitting patterns - can be digitally elaborated into breathtaking, programmable and architecturally viable structures. Internationally renowned architect and researcher Lars Spuybroek has been investigating the relationships between art, architecture and information technology. His students in the Georgia Institute of Technolgy, School of Architecture have contributed their projects in this second book in research and design.
Figure-configuration taxonomies -- Gothic rose windows & traceries -- Leaf venation -- Foam regular to irregular -- Packing-cracking -- Braiding hairdo's -- Celtic knotwork crosses -- Haeckels radiolaria revisited -- Textiles towers & textile façades -- Textile towers -- Radiolaria tower / Jonathan Aprati, Valerie Bolen, Jin Cong Hong & Kim Wadelton -- Wool thread tower / Matt Erwin & Adam Sauer -- Braiding tower / Cameron Bishop & Mara Neumann -- Gothic tower / Sookie Kim & Rae Smith -- Foam tower / Geoffrey Braiman & Dave Beil -- Textile façades -- Crystallized colors / Derek Tao-Han Liu -- Tectonic networking / Adrienne Froemelt & Paul Meyer -- Interlaced / Katherine Giraldo & Atreya Safari & Be Thach -- Fissure / Jacob Porter & Darryl Zuk -- Radiolaria / Tasnouva Habib & Yasin Bulhan -- Gothic / Jennifer Reinhardt.
Includes bibliographical references (p. 41).
Keywords: Architectural design; Architectural design -- Data processing